SISTEM KARANG MEMADU SEBAGAI BENTUK SANKSI ADAT TERHADAP TINDAK POLIGAMI DI DESA ADAT PENGLIPURAN KECAMATAN BANGLI KABUPATEN BANGLI - Endra Irawan, I Wayan (Jurnal Pendidikan Kewarganegaraan Undiksha, 2013)
ABSTRACTThis study aimed to determine whether sanctions reef runway in traditional village forge Penglipuran, and how sanctions mengantisifasi coral mixing in polygamous marriages in the Village People Penglipuran. The data were collected using several methods, including: 1). Interview, 2). Registration documents and 3). Observation. The study used a qualitative descriptive study. The research was conducted in rural communities in the District pakraman Penglipuran Bangli, Bangli district. Informant or source of the data in this study is the village of Pakraman Penglipuran consisting of: 1). Society Pakraman Penglipuran, 2). Bendesa custom Pakraman Penglipuran, 3) Jro Kubayan Pakraman Penglipuran. Determination of the informants in this study was purposive sampling techniques, namely the determination of the respondents according to the purpose. The results showed that: 1). The foundation of the reef sanctions mixing using several grounds will be used as a guide or reference in the application. The foundation such as juridical foundation (awig awig), sociological foundation (people), relegius foundation. 2). Process of mixing rock sanctions in the traditional village Penglipuran it through three stages, the first stage is a call to those who commit acts of polygamy to listen to the exposure of some indigenous prajuru related aspects in the mixing rock sanctions to be received later, when it was still adamant in its stand still like polygamy, then prajuru custom will continue into the second stage of the manufacture of the hut to put a polygamous family is in an area called coral fuse, if the hut is finished created, it will be continued into the third process is the placement of a polygamous family in the hut that has been made by indigenous villagers in the area of the reef thing about mixing.Key words: Customary Sanctions and Follow Polygamy.